The Portuguese in the Orient. - International Centre for Ethnic Studies (2010)
Contributed articles on the history of Sri Lanka under the Portuguese.
Keywords: Portuguese -- Sri Lanka -- History; Sri Lanka -- History -- 16th century; Sri Lanka -- History -- 17th century; India -- History -- 1526-1765.